2013
DOI: 10.1021/la403050c
|View full text |Cite
|
Sign up to set email alerts
|

Electropolymerized Three-Dimensional Randomly Branched EDOT-Containing Copolymers

Abstract: The potential of 2,2';3,2″-terthiophene (3T) as branching units in 3D copolymers is presented with EDOT as an example comonomer. Branched EDOT/3T polythiophenes were prepared by electropolymerization, and their electrochemical and optical properties are discussed. Two different approaches were employed: (i) the direct electropolymerization of a novel branched thiophene monomer (3TE3) consisting of a 3T core that contains three outer EDOT end groups and (ii) the electrochemical copolymerization of a EDOT/3T mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 57 publications
3
23
0
Order By: Relevance
“…Dioxane, N,N-dimethylformamide (DMF) and toluene were dried over 4 Å molecular sieves. 3,6-Dibromothieno [3,2-b]thiophene (1) 36 and 2-tributylstannyl-3,4-ethylenedioxythiophene (5) 37 were synthesized according to the literature procedures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dioxane, N,N-dimethylformamide (DMF) and toluene were dried over 4 Å molecular sieves. 3,6-Dibromothieno [3,2-b]thiophene (1) 36 and 2-tributylstannyl-3,4-ethylenedioxythiophene (5) 37 were synthesized according to the literature procedures.…”
Section: Methodsmentioning
confidence: 99%
“…S19, ESI †). This might indicate that initially the deprotonated/dedoped polymer film undergoes ( partial) protonation during anodic cycling, perhaps, by protons formed by an oxidation of traces of water 48 to be present in the film (or in the solvent). Thiophene-pyridine copolymers with a pyridine ring in the main chain have been previously studied, [49][50][51] and it was shown that the pyridine ring is sufficiently basic to be protonated.…”
Section: Electrochemical Polymerizationmentioning
confidence: 99%
“…The electropolymerization of structures 32 – 34 will be discussed below. An EDOT‐endcapped 3T‐terthiophene ( 35 ) was synthesized in our group and also applied as monomer in electropolymerizations …”
Section: Structurally Well‐defined Branched Thiophenes: From Small Momentioning
confidence: 99%
“…Recently our group published on the synthesis of a related monomer ( 35 , Scheme ) consisting of a 3T core and three attached EDOT end groups . The electropolymerization thereof yields a polymer which has a HOMO‐level lying in between the HOMO‐levels of the polymers P(3T) and PEDOT.…”
Section: Branched Polythiophenesmentioning
confidence: 99%
See 1 more Smart Citation